2008
DOI: 10.1016/j.neuroscience.2008.01.081
|View full text |Cite
|
Sign up to set email alerts
|

Task-dependent encoding of space and events by striatal neurons is dependent on neural subtype

Abstract: The dorsal striatum plays a critical role in procedural learning and memory. Current models of basal ganglia assume that striatal neurons and circuitry are critical for the execution of overlearned, habitual sequences of action. However, less is known about how the striatum encodes task information that guides the performance of actions in procedural tasks. To explore the striatal encoding of task information, we compared the behavioral correlates of striatal neurons tested in two tasks: a Multiple-T-maze task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
94
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 53 publications
13
94
1
Order By: Relevance
“…Previous work has reported that both HC (O'Keefe and Nadel 1978; Redish 1999) and aDLS Schmitzer-Torbert 2004;Yeshenko et al 2004) neurons were spatially tuned on a task in which spatial cues provided information about how to obtain rewards; however, on a spatial task in which spatial cues did not provide information about how to obtain rewards, only HC neurons were spatially tuned (Berke et al 2009;Wikenheiser and Redish 2011) while aDLS neurons were not (Berke et al 2009;Schmitzer-Torbert and Redish 2008). We found that HC and aDLS neurons responded in a similar fashion to spatial context in the present study, such that many neurons in both structures were spatially tuned to one side of the maze or the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has reported that both HC (O'Keefe and Nadel 1978; Redish 1999) and aDLS Schmitzer-Torbert 2004;Yeshenko et al 2004) neurons were spatially tuned on a task in which spatial cues provided information about how to obtain rewards; however, on a spatial task in which spatial cues did not provide information about how to obtain rewards, only HC neurons were spatially tuned (Berke et al 2009;Wikenheiser and Redish 2011) while aDLS neurons were not (Berke et al 2009;Schmitzer-Torbert and Redish 2008). We found that HC and aDLS neurons responded in a similar fashion to spatial context in the present study, such that many neurons in both structures were spatially tuned to one side of the maze or the other.…”
Section: Discussionmentioning
confidence: 99%
“…HC neurons that are spatially tuned form a cognitive map, allowing for integration of past and potential future experiences in order to plan behavior (O'Keefe and Nadel 1978;McNaughton et al 2006;Redish 1999;Wikenheiser and Redish 2015a). Neurons in the dorsolateral striatum also respond to spatial cues Redish 2004, 2008;Yeshenko et al 2004), but only when spatial cues contain information about obtaining rewards (Berke et al 2009;Schmitzer-Torbert and Redish 2008). Neural activity in the dorsolateral striatal neurons is related to specific motor movements and actions DeLong 1985a, 1985b;Carelli and West 1991;Cho and West 1997;Jog et al 1999;Schmitzer-Torbert and Redish 2008), likely ones that have consistently led to reinforcement.…”
mentioning
confidence: 99%
“…Cell type categorization. As described previously, ventral striatal units were assigned to one of three cell type categories: phasically firing neuron (putative medium spiny neuron), high-firing neuron (putative fast-spiking interneuron), or tonically firing neuron, based on spiking statistics (Schmitzer-Torbert and Redish, 2008;van der Meer et al, 2010a). Hippocampal units were separated into putative pyramidal neurons and interneurons based on average firing rate (interneurons, Ͼ2 Hz) (Ranck 1973;Csicsvari et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, these cells have been argued to have a critical role filtering out unwanted actions, and postmortem studies have found a deficit in striatal FSIs in Tourette syndrome (Kalanithi et al, 2005). Several groups studied putative FSIs in awake, behaving animals, identifying them on the basis of characteristic brief waveforms, tonic activity, and high-frequency discharges (Berke et al, 2004;Berke, 2008;Gage et al, 2008;Schmitzer-Torbert and Redish, 2008). In rats, FSIs show complex temporal sequences of activity during choice tasks, and do not normally act as a coordinated cell population with closely linked firing rates, even within striatal microregions (Berke, 2008).…”
Section: Role Of Interneurons In Transforming Cortical Input To Striamentioning
confidence: 99%